On a Constructive Approach for Derivative-Dependent Singular Boundary Value Problems - R. K. Pandey; Amit K. Verma (International Journal of Differential Equations)
We present a constructive approach to establish existence and uniqueness of solution of singular boundary value problem -(p(x)y′(x))′=q(x)f(x,y,py′) for 0<x≤b,y(0)=a,α1y(b)+β1p(b)y′(b)=γ1. Here p(x)>0 on (0,b) allowing p(0)=0. Further q(x) may be allowed to have integrable discontinuity at x=0, so the problem may be doubly singular.